2022
DOI: 10.51847/zaqwktglhh
|View full text |Cite
|
Sign up to set email alerts
|

Comparative between Double Inversion Recovery and Fluid-Attenuated Inversion Recovery Sequences for Detection of Brain Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is the most common chronic inflammatory demyelinating disease of the central nervous system (CNS). MS diagnosis and disease monitoring are mostly based on Magnetic Resonance Imaging (MRI). This study aims to compare a double inversion recovery MRI sequence with a fluidattenuated inversion recovery sequence in Multiple Sclerosis (MS) in the brain. A study was conducted on 75 patients whose aged between 10 and 70 years who were having MS in the brain to compare a double inversion recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…In the supratentorial region a less lesion number were identified on DIR than T2 and FLAIR in different white matter locations. DIR revealed significantly more lesions in the periventricular WM when compared to T2 WI as the results of Abidi et al (23), but in contrary for the FLAIR sequence where shown also by Hamed W et al (24) and Elhussein N et al (26) work. However, DIR showed less deep WM lesions than T2 and FLAIR sequences, in accordance to the study conducted by Hamed W et al (24), and in controversy to the study done by Elnekeidy et al (21).…”
Section: Discussionsupporting
confidence: 56%
“…In the supratentorial region a less lesion number were identified on DIR than T2 and FLAIR in different white matter locations. DIR revealed significantly more lesions in the periventricular WM when compared to T2 WI as the results of Abidi et al (23), but in contrary for the FLAIR sequence where shown also by Hamed W et al (24) and Elhussein N et al (26) work. However, DIR showed less deep WM lesions than T2 and FLAIR sequences, in accordance to the study conducted by Hamed W et al (24), and in controversy to the study done by Elnekeidy et al (21).…”
Section: Discussionsupporting
confidence: 56%